Past, Present and Future of Higher Education Internationalization in Russia - Chamchiyan, Anna (International Higher Education, 2015)
The article provides a historical view of the international dimension of Russian higher education, describing more than seventy years’ history of higher education internationalization in Russia and focusing on approaches, opportunities and initiatives. The aim of the study is to put forward an explanation for the visible imbalance which has arisen over the last fifteen years between the ambitions and facilities of the higher education system in Russia and actual levels of internationalization and competitiveness exhibited by the system.